Fracture toughness investigation of metallic materials using experiment and finite element analysis - Mohd Kamal Mohd Shah (2012)
This research was conducted to determine the plane stress and plane strain fracture toughness of various metallic materials. Compact Tension specimens of a wide range of constant thickness such as 5 mm, 10 mm, 15 mm, 20 mm and 25 mm and various materials used to make comparisons of AISI 1030, AISI 1045, AISI 4320, AISI 4340, Alu 2024-T3 ,Alu 2014-T6. Different thickness and width is the same as the main focus in this study. Specimens have been designed using Computer Aided Design and Computer Numeric Control (CNC) machining with an average surface roughness of 10 microns. Compliance method has been proposed to determine the fracture resistance measurement of metals in experimental work. Precracking is used to introduce the beginning of the crack before the test. Fracture toughness was evaluated by the graph of load and displacement and produced type I and type II curves, which were used for evaluation. Results for different materials have shown the value of 2014-T6-36 MPa is IC K =36 MPa m and the value of cast iron is IC K =23.3 MPa m . This result shows both materials clearly indicate the failure of the current state of plane strain fracture tests at room temperature happen rapidly in the environment. The main contribution to the experimental work has shown that the fracture toughness of five different thicknesses with a constant width of the influence of fixed width over the thickness and increase the influence of plastic deformation region significantly in the early stages of crack growth. The load applied to the thickness of 5 mm 12500 N was compared with 25 mm maximum load of 50000 N to obtain fracture toughness in these materials. Similarly, the critical load increases as thickness increases. The result shows that the plane stress appeared to determine the influence of controlled constant width and thickness of the high plastic deformation around the crack tip generated. For this reason ASTM 399-90 suggested that the strength ratio should be calculated for all differences in thickness. Fracture surface with high magnification has been determined using scanning electron microscopic thickness to determine the effect of fracture surface essentially attributable to changes in the pattern of holes and rivers. This may appear at the crack tip necking material difference. Unstable crack propagation was observed during the exchange between the plane stress plane strain. The finite element analysis (FEA) found the stress distribution based on gradual of von Misses stress to predict the stress stage near to crack tip of the compact tension specimen is highest stress range at the notch tip region. It is seen that the contours of the difference stress range of Von Misses stress distribution along the symmetry plane of the specimen corresponding to maximum loading pin displacement of 0.5 mm for 5 mm and 20 mm. For future studies, metals with high heat resistance using the actual thickness of specimen can be tested. It is proposed that the mesh using less than 0.1 mm.